PSTPIP1‐associated myeloid‐related proteinemia inflammatory syndrome: A rare cause of childhood neutropenia associated with systemic inflammation and hyperzincemia. Issue 1 (10th September 2018) - Hashmi, Saman K.; Bergstrom, Katie; Bertuch, Alison A.; Despotovic, Jenny M.; Muscal, Eyal; Xia, Fan; Bi, Weimin; Marcogliese, Andrea; Diaz, Rosa
Abstract: Neutropenia in pediatric patients can be due to a variety of disorders. We describe two patients who underwent extensive evaluation over many years for arthralgias and moderate neutropenia of unclear etiology. Genetic testing identified a pathogenic variant in PSTPIP1 (proline‐serine‐threonine phosphatase‐interacting protein 1) in both patients. Markedly elevated inflammatory markers and zinc levels confirmed the rare diagnosis of PSTPIP1 ‐associated myeloid‐related proteinemia inflammatory (PAMI) syndrome, tailoring treatment. Neutropenia is common in patients with PAMI syndrome. Unique mutations seen in PAMI syndrome may account for the specific phenotypic features of this disorder.